Anesthetic management of cesarean delivery in parturients with ruptured sinus of Valsalva aneurysm: CARE-compliant 2 case reports and literature review. Issue 19 (May 2017) - Fang, Gang; Li, Man; Li, Jian; Lin, Li; Mei, Wei
Abstract: Rationale: Ruptured sinus of Valsalva aneurysm is rare and dangerous in parturients. Few cases of ruptured SVA in pregnancy are reported, and the anesthetic management for cesarean delivery has scarcely been described. Patient concerns: A parturient at 37-week gestation complained of a sore throat and cough that started 3 days before admission, followed 1 day later by fever, dizziness, breathlessness, and palpitation on exertion. Case two at 36-week gestation complained of a 1-day history of bloating in the lower abdomen. Diagnoses: Full term and preterm parturients with ruptured sinus of Valsalva aneurysm. Interventions: Cesarean deliveries were performed with incremental epidural anesthesia technique under invasive monitoring. Surgical correction of the ruptured sinus of Valsalva aneurysms and ventricular septal defect were performed uneventfully 13 days and 7 days postpartum, respectively, for the 2 cases. Outcomes: No complications were observed in the intra- or postoperative period for both mothers and babies. Lessons: We reviewed the pertinent literature and reached the following conclusions: use of a multidisciplinary team to guide anesthetic management is helpful and necessary; and both general anesthesia and incremental epidural anesthesia can be safely used in parturients with ruptured sinus of Valsalva aneurysm.